Tryptophan Breakdown in Patients with HCV Infection is Influenced by IL28B Polymorphism - Heinz Zoller; Annina Jenal; Albert F. Staettermayer; Sebastian Schroecksnadel; Peter Ferenci; Dietmar Fuchs (MDPI AG, 2015)
Until recently, the standard treatment of chronic hepatitis C virus (HCV) infection was a combination therapy with PEG-IFN-α plus ribavirin. Previous studies have proven that several markers predict the outcome of such therapy, e.g., pretreatment plasma levels of interferon inducible protein IP-10, HCV RNA and IL28B-related single nucleotide polymorphisms (SNP). Altered activity of tryptophan metabolizing enzyme indoleamine 2,3-dioxygenase (IDO) has been also shown in patients suffering from HCV infection. In this study, we investigated whether IL28B SNP in patients infected with HCV is related to the tryptophan breakdown rate. Before therapy, serum tryptophan and kynurenine concentrations were determined in 25 patients with established HCV infection and the kynurenine to tryptophan ratio (KYN/TRP) was calculated as an estimate of the tryptophan breakdown rate. In parallel, neopterin and nitrite concentrations were determined. A significant difference of serum KYN/TRP existed between the three IL28B polymorphism groups: C/C genotype had the highest and T/T genotype had the lowest KYN/TRP (p < 0.05). Likewise, C/C genotype was associated with higher KYN/TRP than non-C/C genotype (p = 0.01). There was a smaller difference between the three groups regarding the absolute kynurenine concentrations, the C/C genotype being associated with higher kynurenine concentrations. None of the other comparisons revealed any statistical significance. In conclusion, patients with C/C genotype presented with the highest tryptophan breakdown rate already before antiretroviral therapy with IFN-α/ribavirin. The differences in tryptophan metabolism might relate to HCV clearance and also to side effects of IFN-α therapy.